2015
DOI: 10.1039/c5cc04322k
|View full text |Cite
|
Sign up to set email alerts
|

Residual metals present in “metal-free” N-doped carbons

Abstract: To date, "metal-free" catalysts originating from graphene and CNTs have been revealed to contain metal impurities. Many types of such "metal-free" carbons have been synthesized by metal-involving methods, and it is urgent to confirm the origin of the catalytic performance. Herein, we verified that residual metals were inevitably present in these N-doped carbons and the catalytic performance for the hydrogen evolution reaction (HER) was due to the remaining metals, present at only a ppm level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…27,30,31 Within this context, one of the most promising catalysts is a carbon material containing Fe-N moieties on the surface (Fe-N-C) which, even with only iron traces, shows a higher catalytic activity. 11,[32][33][34] _ENREF_11 The main active site is believed to be iron coordinated to nitrogen, which has been demonstrated to play a major role in the ORR process. 11,35 Herein, we report on N-doped mesoporous carbon capsules with iron traces as ORR electrocatalyst with remarkable performance and stability under both acid and alkaline conditions.…”
mentioning
confidence: 99%
“…27,30,31 Within this context, one of the most promising catalysts is a carbon material containing Fe-N moieties on the surface (Fe-N-C) which, even with only iron traces, shows a higher catalytic activity. 11,[32][33][34] _ENREF_11 The main active site is believed to be iron coordinated to nitrogen, which has been demonstrated to play a major role in the ORR process. 11,35 Herein, we report on N-doped mesoporous carbon capsules with iron traces as ORR electrocatalyst with remarkable performance and stability under both acid and alkaline conditions.…”
mentioning
confidence: 99%
“…The doped Ns peciesa nd contents were then compared by XPS analysis;t he N1ss pectra revealed four signals corresponding to pyridine N, metal N, pyrrolic N, and graphitic Na t3 98.4, 399.0, 400.1, and 401.0eV, respectively. [36,37] As shown in Figure 5c,t he N1ss pectrum of Co@NCNT-700 mainly possessed 398.4 and 401.0 eV peaks,w hich were indexed to pyridinic Na nd graphitic N, respectively;F e@NCNT-700 mainly had pyridinic Na nd pyrrolic Np eaks at 398.4 and 400.1 eV, owing to insufficient carbonizationo fd icyandiamide catalyzed by Fe at 700 8C. [16][17][18][19] Ac lear difference appeared in the spectrum of Ni@NCNT-700, considering loss of the pyridinic- Np eak and the presence of the 399.0 eV peak (metal N), which suggested strong chemical interactions between Na nd Ni.…”
Section: Resultsmentioning
confidence: 99%
“…Co@NCNT‐700 had the lowest ECSA, but conversely it gave the best electrocatalytic activity, which suggested that the ECSA was not the dominant factor. The doped N species and contents were then compared by XPS analysis; the N 1s spectra revealed four signals corresponding to pyridine N, metal N, pyrrolic N, and graphitic N at 398.4, 399.0, 400.1, and 401.0 eV, respectively . As shown in Figure c, the N 1s spectrum of Co@NCNT‐700 mainly possessed 398.4 and 401.0 eV peaks, which were indexed to pyridinic N and graphitic N, respectively; Fe@NCNT‐700 mainly had pyridinic N and pyrrolic N peaks at 398.4 and 400.1 eV, owing to insufficient carbonization of dicyandiamide catalyzed by Fe at 700 °C .…”
Section: Resultsmentioning
confidence: 99%
“…The same catalyst was investigated for ORR activity, and a high kinetic-limited current density (16.9 mA cm –2 ) and electron-transfer number ( n = 3.7) were obtained which were on par with those attained by Pt/C (17.0 mA cm –2 and 3.8, respectively) (Figure d–e), making it an excellent material for as a bifunctional HER and ORR electrocatalyst. Despite the lack of a meticulous study on the potential impact of metallic impurities in graphene on HER performance, it should be highlighted that the study by Sun demonstrated that residual trace impurities in CNTs were responsible for electrocatalytic behavior of CNTs toward HER …”
Section: Graphene and Related Materials For Hermentioning
confidence: 99%
“…Despite the lack of a meticulous study on the potential impact of metallic impurities in graphene on HER performance, it should be highlighted that the study by Sun demonstrated that residual trace impurities in CNTs were responsible for electrocatalytic behavior of CNTs toward HER. 107 Separately, Chen et al explored a N,S-doped graphene as HER electrocatalyst, achieving HER performance parameters which were comparable to that of MoS 2 . 108 An overpotential of 280 mV (vs RHE) at −10 mA cm −2 and Tafel slope of 80.5 mV dec −1 were obtained, and the HER performance was attributed to the close proximity of negatively charged S dopant and positively charged N dopant at a defect site on graphene, enabling fast electron transport route for HER.…”
Section: Graphene and Related Materials For Hermentioning
confidence: 99%